2008
DOI: 10.1074/jbc.m801035200
|View full text |Cite|
|
Sign up to set email alerts
|

Down-regulation of miR-1/miR-133 Contributes to Re-expression of Pacemaker Channel Genes HCN2 and HCN4 in Hypertrophic Heart*

Abstract: Cardiac hypertrophy is characterized by electrical remolding with increased risk of arrhythmogenesis. Enhanced abnormal automaticity of ventricular cells contributes critically to hypertrophic arrhythmias. The pacemaker current I f , carried by the hyperpolarization-activated channels encoded mainly by the HCN2 and HCN4 genes in the heart, plays an important role in determining cardiac automaticity. Their expressions reportedly increase in hypertrophic and failing hearts, contributing to arrhythmogenesis under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 40 publications
5
127
0
1
Order By: Relevance
“…Professor Yang provided evidence that miR-1 is overexpressed in patients with coronary artery dis-npg ease, and that overexpression of miR-1 in normal or infarcted rat hearts was found to exacerbate arrhythmogenesis. His data supported the suggestion that miRNAs are a potential anti-arrhythmic target [20].…”
Section: Cell Death -Good Bad and The Mechanismssupporting
confidence: 69%
“…Professor Yang provided evidence that miR-1 is overexpressed in patients with coronary artery dis-npg ease, and that overexpression of miR-1 in normal or infarcted rat hearts was found to exacerbate arrhythmogenesis. His data supported the suggestion that miRNAs are a potential anti-arrhythmic target [20].…”
Section: Cell Death -Good Bad and The Mechanismssupporting
confidence: 69%
“…17 Another pacing-related gene, HCN2, was a target of miR-133 and upregulated in the hypertrophic state associated with depressed miR-133. 18 On the basis of the established role for miR-133 in cardiac tissue function, we hypothesized that inhibiting this miRNA increases force production by skeletal muscle cells in threedimensional (3D) cultures by promoting differentiation. We previously showed that a collagen gel-based skeletal muscle system was successfully able to form mature, differentiated muscle in a 3D model.…”
Section: Introductionmentioning
confidence: 99%
“…Arrhythmias arise due to heart disease or mutation in ion channel genes, however, miRNAs, such as miR-1 and miR-133 have been implicated to function in cardiac conduction system. The involvement of miR-1 in cardiac conductance was further confirmed by over expression studies in normal and infarcted rat hearts so as upregulation of miR-1 in individuals with coronary heart disease [145,146]. Myocardial vascularization subsequent MI needs signaling by angiogenic growth factors, such as vascular endothelial growth factor and fibroblast growth factor.…”
Section: Mirnas and Cardiovascular Diseasesmentioning
confidence: 75%